Prototype Sensor Parking Otomatis Pada Area Blind-Spot Kendaraan Menggunakan Mikrokontroler - Rafika Sari; Herlawati Herlawati; Fata Nidaul Khasanah; Prima Dina Atika (Journal of Information System Research (JOSH), 2022)
The growth of four-wheeled private vehicle users in Indonesia is quite rapid in the last few years. The problem that then arises from this situation is that not a few vehicle users park their vehicles randomly or not at the right location in the parking area. This is because the driver is a novice driver or an elderly driver so that he is not optimal in predicting the blind-spot area when parking the vehicle. In this study, a prototype of an automatic parking sensor system will be made where the vehicle will receive information on the distance of the vehicle to the surrounding object. The microcontroller in this system uses Arduino UNO R3 and HCR-04 sensor. The software used in this system is designed using the Arduino Uno IDE programming. The system is made with the provisions of placing sensors on the left side of the minibus car (blind-spot area) and a parking system for parallel parking locations (left-right). The system is designed to warn the driver about the distance between the car and surrounding objects by utilizing ultrasonic waves. The distance reading by the sensor is accurate at a distance of 2 – 40 cm. The effective sensor measurement distance is 2-3 cm. With this automatic parking sensor system, it is easier for novice or elderly drivers, as well as other drivers, to park their cars automatically, so that the vehicle parking process becomes faster and more accurate